The Papuan Languages of Timor, Alor and Pantar (Volume 2) - Yunus Sulistyono (Masyarakat Linguistik Indonesia, 2020)
Title : The Papuan Languages of Timor, Alor and Pantar (Volume 2) ISBN : 978-1-61451-906-5, Hard cover Editor : Antoinette Schapper Publisher : De Gruyter, 2017, 358 pp.